(untitled) (CSIAM Transactions on Applied Mathematics, 2020)
This work is devoted to a review of our recent studies in the modeling and computation of nano optical devices. Motivated by technological advances at nano scale, to quantitatively understand the mechanism and improve the designing, we make an effort to model nano optical systems involving multiple physical processes across different time and space scales, and develop multiscale and adaptive numerical methods for simulation. Challenges on rigorous analysis of the models and algorithms are also discussed.